Elevated plasma levels of D-serine in some patients with amyotrophic lateral sclerosis - Lee, Aven; Arachchige, Buddhika Jayakody; Henderson, Robert; Pow, David; Reed, Sarah; Aylward, James; McCombe, Pamela Ann (Amyotrophic lateral sclerosis and frontotemporal degeneration, 2021)
D-serine is an endogenous co-agonist with glutamate for activation of the N-methyl-D-aspartate receptor (NMDAR). D-serine exacerbates neuronal death and is elevated in the spinal cord from patients with sporadic/familial ALS. The present study was undertaken to examine whether plasma levels of D-serine of patients with ALS are different from those of healthy controls. Levels of D-serine in plasma (30 patients and 30 controls) were measured by high-performance liquid chromatography mass spectrometry. Plasma levels of D-serine in ALS patients (mean 39.27 ± 28.61 ng/ml) were significantly higher (p = 0.0293) than those of healthy control subjects (mean 21.07 ± 14.03 ng/ml) as well as previously reported values for healthy controls; ∼43% of patients had plasma D-serine levels that were 2 to 4-folds higher than those of controls. There was no association of plasma D-serine levels with disability, the duration of disease or with the age of subjects. In conclusion, we show that D-serine levels are elevated in the plasma of some ALS patients. Since D-serine serves as a co-agonist/activator of NMDAR, increases in D-serine could have a direct influence on glutamatergic neurotransmission and potentially contribute to excitotoxicity in some ALS patients.